2017
DOI: 10.15448/1981-2582.2017.2.26889
|View full text |Cite
|
Sign up to set email alerts
|

Formação para a ética em pesquisa: um olhar para os programas de pós-graduação em Educação

Abstract: Este artigo está licenciado sob forma de uma licença Creative Commons Atribuição 4.0 Internacional, que permite uso irrestrito, distribuição e reprodução em qualquer meio, desde que a publicação original seja corretamente citada. http://creativecommons.org/licenses/by/4.0/deed.pt_BR Formação para a ética em pesquisa: um olhar para os programas de pós-graduação em Educação AbstRActThe attention of Brazilian education researchers for the debates, studies and researches on research ethics is something recent. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
1
0
9
Order By: Relevance
“…Brooks, Te Riele, & Maguire (2014), in "Ethics and Education Research", point to the relevance of ethical discussions in education based on real situations experienced by researchers. Despite this sensitivity in the field of education, a study by Nunes (2017) has revealed the limited inclusion of research ethics in graduate programs in Brazil. This study analyzed 8,892 subjects in 37 education programs and found that only 0.78% (n=69) of them include research ethics in their course syllabus.…”
Section: Bridging "Two Cultures" Of Research On Humans Through a Heat...mentioning
confidence: 99%
“…Brooks, Te Riele, & Maguire (2014), in "Ethics and Education Research", point to the relevance of ethical discussions in education based on real situations experienced by researchers. Despite this sensitivity in the field of education, a study by Nunes (2017) has revealed the limited inclusion of research ethics in graduate programs in Brazil. This study analyzed 8,892 subjects in 37 education programs and found that only 0.78% (n=69) of them include research ethics in their course syllabus.…”
Section: Bridging "Two Cultures" Of Research On Humans Through a Heat...mentioning
confidence: 99%
“…Para melhor compreensão, elaboramos a Tabela 1 para ilustrar os achados descritos acima. Desse modo, em especial, a partir da análise das 36 teses com necessidade de submissão e que não foram submetidas ao CEP/CONEP, podemos concluir conforme Nunes (2017), que é necessário avançar no debate sobre a ética na formação do pesquisador, pois os programas de pós-graduação devem primar pela qualidade e confiabilidade das pesquisas. Na educação, existe apenas uma regulamentação da ética em pesquisa com seres humanos para as duas grandes áreas: 1) Biomédica e 2) Ciências Humanas e Sociais.…”
Section: Análise Quantitativa E Qualitativaunclassified
“…2021 | e-34020 No presente estudo, a ética é entendida como um elemento necessário nas pesquisas envolvendo seres humanos com vista a resguardar a dignidade e os direitos dos participantes. Goergen (Duarte, 2017;Fagiani & França, 2015;Fare et al, 2014;Franco, 2015;Grisotti, 2015;Lima, 2015;Mello, 2016;Minayo, 2015;Nunes, 2017;Severino, 2015). O capítulo V evidencia a necessidade de assegurar ao participante da pesquisa os cuidados necessários para a minimização dos riscos e a sua devida proteção, partindo do pressuposto que "toda pesquisa com seres humanos envolve risco em tipos e gradações variados" (Brasil, 2013, p. 7).…”
Section: Metodologia Da Pesquisaunclassified